2019
DOI: 10.1186/s12199-019-0764-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to household smoking and dental caries in preschool children: a cross-sectional study

Abstract: BackgroundWe aimed to examine the association of exposure to environmental tobacco smoke with dental caries among preschool children. Exposure to environmental tobacco smoke was assessed in terms of urinary cotinine concentrations and pack-years of exposure to smoking by parents and other family members at home.MethodsThis cross-sectional study included 405 preschool children aged 3–6 years from two preschools in Japan in 2006. Information on the smoking habits of family members living with the child was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 27 publications
6
20
0
5
Order By: Relevance
“…Province is much higher than that in Japanese (31.1%) 9 and English children (31.7%). 10 Compared with more developed countries such as Japan and England, Zhejiang is slower in terms of oral health promotion and treatment, which falls behind its economic development, 13 analysis showed that the prevalence of ECC increased significantly with age.…”
Section: The Prevalence Of Ecc In Children Aged 3-5 Years In Zhejiangmentioning
confidence: 71%
See 3 more Smart Citations
“…Province is much higher than that in Japanese (31.1%) 9 and English children (31.7%). 10 Compared with more developed countries such as Japan and England, Zhejiang is slower in terms of oral health promotion and treatment, which falls behind its economic development, 13 analysis showed that the prevalence of ECC increased significantly with age.…”
Section: The Prevalence Of Ecc In Children Aged 3-5 Years In Zhejiangmentioning
confidence: 71%
“…Among a total of 2700 children enrolled in this study, 1909 children experienced tooth decay or secondary caries after filling (dmft > 0). The prevalence of ECC in children aged 3‐5 years in Zhejiang Province is much higher than that in Japanese (31.1%) 9 and English children (31.7%) 10 . Compared with more developed countries such as Japan and England, Zhejiang is slower in terms of oral health promotion and treatment, which falls behind its economic development, 13 thus leading to a higher incidence of caries.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, this study revealed the relationship between lifestyle behaviors, such as skipping of breakfast, and the status of caries in children, although no significant association was shown in the regression analysis. As a severe status of caries and lifestyles at home often reflect other social aspects or family environment [41, 42], further studies considering the overall lifestyles of children and attitudes of caretakers [11] are required.…”
Section: Discussionmentioning
confidence: 99%